2007
DOI: 10.1097/qad.0b013e328285da15
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of autoreactivity of the broadly neutralizing HIV antibodies 4E10 and 2F5 and retrospective analysis of clinical safety data

Abstract: Monoclonal antibody 4E10 but not 2F5 or 2G12 showed autoreactive binding specificities. Infusion of 4E10 resulted in transient low anticardiolipin titers. Although an increased thromboembolic risk cannot definitely be excluded, this risk appears to be low and likely depend on underlying disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…Explicitly, the hypothesis is that the MPER antigenically mimics cardiolipin, an autoantigen; therefore, MPER immunogens fail to induce neutralizing anti-MPER antibodies because B cells with autoreactive antibody specificities are negatively regulated by tolerance mechanisms. However, we and others have found that 2F5 does not bind to CL in diagnostic assays of antiphospholipid syndrome or to liposome surfaces (21,25,28), which suggests that difficulties in eliciting neutralizing antibodies against MPER immunogens is not generally related to CL reactivity. Furthermore, it has been shown that antibody responses can be elicited to MPER immunogens, only that these antibodies are not potently neutralizing (44), suggesting again that tolerance is not the issue, but some qualitative difference between neutralizing and "nonneutralizing" MPER antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explicitly, the hypothesis is that the MPER antigenically mimics cardiolipin, an autoantigen; therefore, MPER immunogens fail to induce neutralizing anti-MPER antibodies because B cells with autoreactive antibody specificities are negatively regulated by tolerance mechanisms. However, we and others have found that 2F5 does not bind to CL in diagnostic assays of antiphospholipid syndrome or to liposome surfaces (21,25,28), which suggests that difficulties in eliciting neutralizing antibodies against MPER immunogens is not generally related to CL reactivity. Furthermore, it has been shown that antibody responses can be elicited to MPER immunogens, only that these antibodies are not potently neutralizing (44), suggesting again that tolerance is not the issue, but some qualitative difference between neutralizing and "nonneutralizing" MPER antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has become increasingly clear that 4E10 binds to lipids in the absence of the MPER (21,(23)(24)(25)(26)(27)(28)(29). These studies have generated models of 4E10 epitope recognition (21,23), but they have not yet fully addressed which antibody region(s) bind lipid and, of particular importance for vaccine design, whether lipid interaction is an essential component of MPER-mediated neutralization.…”
mentioning
confidence: 99%
“…The latter finding has led to the suggestion that 2F5 might be autoreactive (12), although passive transfusion of 2F5 does not appear to have deleterious effects (38) and 2F5 failed to react in some clinically based assays for autoreactive lipid antibodies (31,39). The crystal structures of the 2F5 antibody in complex with its gp41 MPER epitope revealed that, despite the 22-residue length of the 2F5 heavy chain third complementarity-determining region (CDR H3) loop, contacts with the gp41 MPER peptide are made predominantly at the loop base.…”
mentioning
confidence: 99%
“…4E10, in particular, has affinity for lipids in addition to its peptide binding capacity (2,4,32,66,69,75,77). The affinity of 2F5 for lipids is controversial (38,46,66,70,77,85).…”
mentioning
confidence: 99%